2009
DOI: 10.1111/j.1365-3164.2009.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequent detection of papillomavirus DNA in clinically normal skin of cats infected and noninfected with feline immunodeficiency virus

Abstract: Feline cutaneous squamous cell carcinomas (SCCs) often contain felis domesticus papillomavirus type 2 (FdPV-2) DNA. While this may suggest FdPV-2 causes feline SCC development, the proportion of cats that are asymptomatically infected by this PV is unknown. Infection by feline immunodeficiency virus (FIV) is associated with high rates of cutaneous SCC development, possibly due to increased PV infection. This study examines the frequency of cutaneous asymptomatic FdPV-2 infections in cats and compares the rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 18 publications
0
39
0
Order By: Relevance
“…PV DNA was amplified from 50% of the SCCs in the present study. However, as PVs can asymptomatically infect feline skin, 28 the detection of PV DNA within a cutaneous SCC does not prove that the virus influenced neoplasm development. As has been reported, 22 PV DNA was detected in the present study more frequently in SCCs from UV-protected areas than in SCCs from UV-exposed skin.…”
Section: Discussionmentioning
confidence: 99%
“…PV DNA was amplified from 50% of the SCCs in the present study. However, as PVs can asymptomatically infect feline skin, 28 the detection of PV DNA within a cutaneous SCC does not prove that the virus influenced neoplasm development. As has been reported, 22 PV DNA was detected in the present study more frequently in SCCs from UV-protected areas than in SCCs from UV-exposed skin.…”
Section: Discussionmentioning
confidence: 99%
“…FcaPV-2 is thought to cause premalignant skin lesions including viral plaques and Bowenoid in situ carcinomas, as these lesions frequently contain FcaPV-2 DNA and cytopathic changes consistent with papillomavirus replication (Munday & Peters-Kennedy, 2010;Munday et al, 2007). Additionally, FcaPV-2 DNA has been found in skin swabs from normal cats, suggesting that subclinical infections may be common (Munday & Witham, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Asymptomatic PV infections are common in many species, 2 and more than half of cats are asymptomatically infected by Feline papillomavirus type 2 (FDPV-2). 15 Most PVs appear to be species-specific, 8 and recent investigations of equine sarcoids, a neoplasm that shares many features with feline sarcoids, 9 revealed that the causative PV is often present on equine skin. 3,16 Therefore, it was hypothesized that FeSarPV, frequently and asymptomatically, infects cats but rarely causes disease.…”
mentioning
confidence: 99%
“…Second, asymptomatic PV infection of feline skin is common. 15 Consensus primers may have amplified DNA from PVs other than FeSarPV making subsequent sequencing necessary. Additional sequencing was avoided in the present study by using specific primers.…”
mentioning
confidence: 99%